1975
DOI: 10.7883/yoken1952.28.157
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Clostridium Botulinum Type B and E Progenitor Toxins to Some Clostridial Sulfhydryl-Dependent Proteases

Abstract: SUMMARY:Sulfhydryl-dependent proteases produced by Clostridium botulinum types A, B, and F, Clostridium histolyticum, Clostridium sporogenes and Clostridium perfringens activate preferentially type E over type B progenitor toxin but less efficiently than trypsin. The results explain why activable toxin is demonstrable in culture of a strongly proteolytic type B strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Both preparations required a thiol-reducing agent for full activity, were very active against arginine bonds, were sensitive to inhibition by EDTA, and had pH optima of 6 to 6.5. The preparation described by Ohishi et al (21) differed from ours, however, in its high esterase activity, relative to amidase activity, and its ability to partially activate (i.e., 68% full activity) type E progenitor toxin. The amidase (protease) that we purified showed much greater amidase activity than esterase activity and was unable to nick or activate type B or E NTs (6).…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…Both preparations required a thiol-reducing agent for full activity, were very active against arginine bonds, were sensitive to inhibition by EDTA, and had pH optima of 6 to 6.5. The preparation described by Ohishi et al (21) differed from ours, however, in its high esterase activity, relative to amidase activity, and its ability to partially activate (i.e., 68% full activity) type E progenitor toxin. The amidase (protease) that we purified showed much greater amidase activity than esterase activity and was unable to nick or activate type B or E NTs (6).…”
Section: Resultscontrasting
confidence: 57%
“…The 1,000-fold-purified amidase had some properties similar to those found in the crude protease preparation ob- (21). Both preparations required a thiol-reducing agent for full activity, were very active against arginine bonds, were sensitive to inhibition by EDTA, and had pH optima of 6 to 6.5.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…These results indicate that purified a-toxin possessing Zn2+ is rather resistant to various proteases. DISCUSSION There have been many reports (1,3,6,8,10,17) dealing with various microbial proteases, but little information (5,15) is available on proteases of C. perfringens type A. Therefore, workers have inconsistent views and opinions regarding production, properties, and roles ofthe proteases produced by this organism.…”
Section: Zn2cmentioning
confidence: 99%
“…Clostridium botulinum types A through F can be grouped into two according to their proteolytic activities; all type A and some type B and F strains are proteolytic, while all type C, D and E and some type B and F strains are non proteolytic. Proteolytic C. botulinum types A, B and F produce sulfhydryl dependent protease (trypsin-like or clostripain-like enzyme) and the protease purified from cultures of proteolytic strains activates type B and E toxins (DasGupta, 1971;DasGupta and Sugiyama, 1972a;Ohishi, Okada and Sakaguchi 1975;Ohishi and Sakaguchi, 1977a). It was also demonstrated that the toxin molecules (the toxic component of the progenitor toxin) purified from proteolytic C. botulinum types A, B and F and reduced with mercaptoethanol dissociated into two polypeptide chains in SDS gel electrophoresis (DasGupta and Sugiyama, 1972b;Sugiyama, DasGupta and Yang, 1973).…”
Section: ) Arthropodsmentioning
confidence: 99%